Tuturan di Wilayah Perbatasan:Studi Kasus di Daerah Leksono, Kabupaten Wonosobo - Apisari, Esti; Suryadi, M.; Nurhayati (Sutasoma : Jurnal Sastra Jawa, 2024)
Topography is one of the factors that influence language development in an area. Leksono is one of the areas located on the border of Wonosobo and Banjarnegara regency. The people of Wonosobo generally spoke Solo-Yogya dialect, while Banjarnegara people used Banyumas dialect. This fact caused the people of Leksono to encounter the two dialects. The stersebutation affected the speech of Leksono people. This research aims to describe the speech of Leksono people. This article belongs to descriptive qualitative. The method used was listening with note-taking technique. The data were utterances in the community itself. When there was a formal or informal event, the dialog in the community was recorded and transcribed. Based on the analysis, in the daily conversations and informal settings, the dominant speech was the ngoko variety of Banyumas dialect. However, the Solo-Yogya dialect ngoko variety was also acceptable. Unlike the ngoko variety, the krama variety that develops in Leksono was the Solo-Yogya dialect. This variety was used to speak to people who were respected. Meanwhile, in the fields of art and religion, the Solo-Yogya dialect was also dominantly used. In fact, the dialect is not only used in the krama variety. The ngoko variety also uses the Solo-Yogya dialect when the Leksono community makes art. This shows the hegemony of Solo-Yogya over the Leksono community.